2013
DOI: 10.1186/1475-2875-12-33
|View full text |Cite
|
Sign up to set email alerts
|

Travel history and malaria infection risk in a low-transmission setting in Ethiopia: a case control study

Abstract: BackgroundMalaria remains the leading communicable disease in Ethiopia, with around one million clinical cases of malaria reported annually. The country currently has plans for elimination for specific geographic areas of the country. Human movement may lead to the maintenance of reservoirs of infection, complicating attempts to eliminate malaria.MethodsAn unmatched case–control study was conducted with 560 adult patients at a Health Centre in central Ethiopia. Patients who received a malaria test were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
86
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(105 citation statements)
references
References 25 publications
12
86
2
1
Order By: Relevance
“…The findings are consistent with others reported that ownership or use of an ITN showed lack of protective effect against malaria in the country [4], [25], [29]. However, spraying IRS on the walls of houses reduced the risk of malaria [3], [29], [30].…”
Section: Discussionsupporting
confidence: 91%
“…The findings are consistent with others reported that ownership or use of an ITN showed lack of protective effect against malaria in the country [4], [25], [29]. However, spraying IRS on the walls of houses reduced the risk of malaria [3], [29], [30].…”
Section: Discussionsupporting
confidence: 91%
“…Risk factors can be identified through analysis of routine data; however, risk assessments are more accurate when made using case-control study methods [41], such as are frequently used for outbreak investigations [42].…”
Section: Considerations For Successful Acd Implementationmentioning
confidence: 99%
“…Case–control studies can effectively identify risk factors and are recommended by the WHO for malaria elimination settings with low case numbers [16, 6265]. However, because case–control studies typically include individuals diagnosed at health facilities or sentinel sites, inference may be limited to symptomatic malaria.…”
Section: Introductionmentioning
confidence: 99%